lncRNA NEAT1 Downregulation Ameliorates the Myocardial Infarction of Mice by Regulating the miR-582-5p/F2RL2 Axis - Zhenhua Wu; Yunpeng Bai; Yujuan Qi; Chao Chang; Yan Jiao; Yaobang Bai; Zhigang Guo (Cardiovascular Therapeutics)
Background. This study is aimed at effectively investigating the role of coagulation factor II thrombin receptor like 2 (F2RL2) in myocardial infarction (MI) as well as the upstream regulatory miRNA and lncRNA. Methods. Regulatory genes of F2RL2 were analyzed using StarBase and verified by dual-luciferase reporter assay. The MI mouse model was established. The left ventricular ejection fraction (EF) and fractional shortening (FS) were examined by echocardiography. The infarct area, pathological changes, and cell apoptosis in mouse myocardial tissue were evaluated using triphenyltetrazolium chloride and Evans blue, hematoxylin-eosin, and TUNEL staining assays. Oxygen-glucose deprivation- (OGD-) induced human cardiac myocytes (HCMs) were cultured and transfected. The cell viability, proliferation, and apoptosis were determined by CCK-8, EdU staining, and flow cytometry assays. The expressions of F2RL2, miR-582-5p, and nuclear paraspeckle assembly transcript 1 (NEAT1) in myocardial tissues and HCMs were quantified by qRT-PCR or Western blot. Results. NEAT1 sponged miR-582-5p which targeted F2RL2. NEAT1 and F2RL2 were highly expressed while miR-582-5p was lowly expressed in MI mice. F2RL2 downregulation prevented the reduction in EF and SF and the elevation in infarct area and cell apoptosis of MI mice. Both F2RL2 and NEAT1 downregulations reversely modulated the decreased viability and proliferation and the increased apoptosis of OGD-induced HCMs, while miR-582-5p inhibitor did oppositely. NEAT1 silencing upregulated miR-582-5p level but downregulated F2RL2 level. miR-582-5p inhibitor upregulated the F2RL2 level. The role of NEAT1 silencing in OGD-induced HCMs was reversed by miR-582-5p inhibitor whose effect was further offset by F2RL2 downregulation. Conclusion. NEAT1 downregulation ameliorates MI by regulating the miR-582-5p/F2RL2 axis, providing novel biomarkers for MI treatment.